Potent bioactive methanolic extract of wild orange (Citrus macroptera Mont.) shows antioxidative, anti-inflammatory, and antimicrobial properties in in vitro, in vivo, and in silico studies - Lala, Mousikha (2021)
At 200 μg/ml concentration, CML significantly scavenges reactive oxygen species (ROS) which was generated on HepG2 cell line. CML showed 71% anti-inflammatory activity (p ≤ 0.001) against carrageenan-induced paw edema in albino Wistar rats. CML extract is very effective against staphylococcus sp. than Klebsiella sp. In the docking analysis, the proximadiol and menthone had − 5.6 kcal/mol and − 5.7 kcal/mol binding affinity with the protein NF-ҡB.